COST-PUSH INFLATION DAN KEBIJAKAN MONETER SYARI’AH: IMPLIKASI BAGI EKONOMI INDONESIA - Ilham Khoirurrozikin; Ainur Aisyah; Bray Nero Valerian; Kevin Dwi Ramadhani; Amalia Nuril Hidayati (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to explain the concept of cost-push inflation, understand the principles of Islamic monetary policy, and analyze its effectiveness in addressing inflationary pressures. This study employed library research with a qualitative approach, drawing on journals, books, and contemporary Islamic economics and macroeconomic literature. The results indicate that Islamic monetary policy has the potential to be more adaptive to cost-push inflationary pressures because it rejects speculative practices and bases economic activity on a stable and productive value basis. Consequently, this policy not only has the potential to suppress cost-push inflation but also supports price stability, strengthens the resilience of the real sector, and safeguards long-term public welfare.